Genetic Variant of PP2A Subunit Gene Confers an Increased Risk of Primary Liver Cancer in Chinese - Wang Y; Huang Q; Huang X; Zhao H; Guan B; Ban K; Zhu X; Ma Z; Tang Y; Su Z; Nong Q (Dove Medical Press, 2021)
Youxin Wang,1,* Qiuyue Huang,1,* Xinglei Huang,1 Huiliu Zhao,2 Bin Guan,1 Kechen Ban,3 Xuefeng Zhu,1 Zhixing Ma,1 Yanmei Tang,1 Zhaohui Su,1 Qingqing Nong1 1Department of Environmental Health, School of Public Health, Guangxi Medical University, Nanning, 530021, People's Republic of China; 2Department of Clinical Laboratory, The Affiliated Tumor Hospital of Guangxi Medical University, Nanning, 530021, People's Republic of China; 3Department of Pathology, The University of Texas M. D. Anderson Cancer Center, Houston, TX, 77030, USA*These authors contributed equally to this workCorrespondence: Qingqing NongDepartment of Environmental Health, School of Public Health, Guangxi Medical University, Nanning, 530021, People's Republic of ChinaTel +86-771-5358146Fax +86-771-5350823Email nnqq@gxmu.edu.cnBackground: Protein phosphatase 2A (PP2A, a serine/threonine phosphatase) is frequently inactivated in many types of cancer, including primary liver cancer (PLC). Genetic variations in PP2A subunits have been reported to be associated with the risk of many types of cancer but rarely in PLC. This study aims to assess the association between functional polymorphisms of PP2A subunit genes and the risk of PLC in Chinese.Methods: In a case-control study with a total of 541 PLC patients and 547 controls in Guangxi province of Southern China, we genotyped six putatively functional polymorphisms (rs10421191G>A, rs11453459del>insG, rs1560092T>G, rs7840855C>T, rs1255722G>A and rs10151527A>C) of three PP2A subunit genes (PPP2R1A, PPP2R2A and PPP2R5E) using matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry platform.Results: The rs11453459insG variant genotypes (ins/ins+del/ins) of PPP2R1A were found to be significantly associated with an increased risk of PLC compared with the del/del genotype (adjusted OR = 1.290, 95% CI = 1.009- 1.650), and the number of insert G allele worked in a dose-dependent manner (Ptrend= 0.007). The stratified analysis showed that the effects of rs11453459insG variant genotypes were more evident in the subgroup who drink pond-ditch water (adjusted OR = 3.051, 95% CI = 1.264- 7.364) than those never drink (P = 0.041). The carriers of rs11453459 del/ins genotype had a significantly lower level of PPP2R1A mRNA expression in liver cancer tissues than those of the del/del genotype (P = 0.021). Furthermore, we used microcystin-LR, a carcinogen presents in the pond-ditch water, to treat human peripheral blood mononuclear cells and found that the cells from carriers of rs11453459insG variant genotypes induced more DNA oxidative damages than those from the del/del genotype carriers (P < 0.001).Conclusion: These findings suggest that the PPP2R1A rs11453459del>insG polymorphism is associated with an increased risk of PLC, especially for persons with a history of drinking pond-ditch water. This insertion/deletion polymorphism may be a susceptible biomarker for PLC in Chinese.Keywords: PP2A, primary liver cancer, insertion/deletion polymorphism, pond-ditch water